2002
DOI: 10.4049/jimmunol.169.1.393
|View full text |Cite
|
Sign up to set email alerts
|

The Epistatic Interrelationships of IL-1, IL-1 Receptor Antagonist, and the Type I IL-1 Receptor

Abstract: Mice lacking the gene for the IL-1R antagonist (IL-1ra) show abnormal development and homeostasis as well as altered responses to infectious and inflammatory stimuli. A reduction in the level of IL-1 signaling, either by deletion of the receptor or increased expression of IL-1ra, does not affect development or homeostasis, but does alter immune responses. In this study we use genetic epistasis to investigate the interdependence of selected genes in the IL-1 family in the regulation of these developmental and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 30 publications
6
36
0
Order By: Relevance
“…2) Irikura et al (38) have characterized the inflammatory phenotype of IL-1Ra Ϫ/Ϫ mice and have crossed them with IL-1 receptor knock-out animals. These experiments have revealed that the low body weight of IL-1Ra-deficient mice can be rescued either by deleting the IL-1 receptor or by reintroducing a transgene coding for IL-1Ra.…”
Section: Discussionmentioning
confidence: 99%
“…2) Irikura et al (38) have characterized the inflammatory phenotype of IL-1Ra Ϫ/Ϫ mice and have crossed them with IL-1 receptor knock-out animals. These experiments have revealed that the low body weight of IL-1Ra-deficient mice can be rescued either by deleting the IL-1 receptor or by reintroducing a transgene coding for IL-1Ra.…”
Section: Discussionmentioning
confidence: 99%
“…acute respiratory distress syndrome have been shown to have increased IL-1ra:IL-1␤ ratio in bronchoalveolar lavage fluid (28). It appears that the sole essential function of IL-1ra is the competitive inhibition of the IL-1RI (20). Previous studies have shown that from 50-to 500-fold excess of IL-1ra to IL-1␤ is necessary to inhibit IL-1␤'s action on effector cells in vitro (15).…”
Section: Discussionmentioning
confidence: 99%
“…Irikura et al 16 have shown that the induced phenotypic features and general malaise observed in C57BL/6 Il1rn Ϫ/Ϫ animals are suppressed by overexpression of IL-1ra or by elimination of IL-1R1. We show that a single functional copy of the IL-1R1 gene (Il1r1) is essential for the pathology of IL-1ra deficiency, which implicates IL-1 as the mediator of the disease process.…”
Section: Discussionmentioning
confidence: 99%